Aspiration in Nepali - Chalise, Krishna Prasad (Nepalese Linguistics, 2018)
This experiment studies the effect of aspiration on PVD, CD, ACT and SA of the Nepali plosives and finds that the voiced aspirates (also called breathy voiced) share the features of both the voiced plosives and aspirated plosives. So, they are voiced aspirates phonetically. To define aspiration in terms of voicing lag is inappropriate because it is found in both the voiceless and voiced plosives in Nepali.